IMPLEMENTASI KOMBINASI 3IC Tools SEBAGAI PENENTU OPTIMASI PENGENDALIAN PERSEDIAAN MINYAK GORENG - Riani, Lilia Pasca; Purnomo, Hery (BISMA: Jurnal Bisnis dan Manajemen, 2019)
The purposes of this study are: (1) to classify the brand of the cooking oil product in the class A category using ABC method, (2) to identify the safety stock level of the inventory, and (3) to determine the highest reorder point for the cooking oil product in class A. This research is a descriptive research with quantitative approach. Data were collected based on observational studies and interviews. Data analysis was performed using 3IC tools divided into three stages: first, ABC analysis to classify product class in class A, B, or C; second, calculating the safety stock level for the class A cooking oil; and third, determining the reorder point. The results showed that of the 86 cooking oil’s brands and packagings, 28 brands were classified in class A; the highest safety stock calculation was on Sedaap brand cooking oil packaged in 2 liter refill, and the highest reorder point level was on the Rosebrand cooking oil packaged in 1 liter refill. Keywords : Cooking oil, 3IC tools, ABC method, safety stock, reorder point.